HIDUP MENGGEREJA ORANG MUDA KATOLIK DALAM ARUS MODERNISASI - Darmawan, Fransiscus Xaverius Riski; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
Life of the Catholic Church in the current of modernization needs to be seriously considered by the young Catholics. It is because the future of the Catholic Church depends on the quality of the Catholic young in a parish or region. The current of modernization poses a great challenge for the young Catholics because modernization can be a means of facilitating the involvement of the young Catholics in the life of the Church. On the other hand, the current of modernization can also be alienating young people from the Church. The Catholics young should be able to develop and utilize those five duties of the Church ministery in the current of modernization as best as possible. The development and utilization of those Church ministery within modernization require the Catholics young to operationalize those Church ministery which are koinonia, kerygma, martyria, liturgia, and diakonia. The informants of the study were the Catholics young of the Immaculate Saint Mary Parish, Surabaya. The study was conducted using a qualitative method. The objective of the study is to examine the perception of the young Catholics on how to develop and utilize the duties of Church ministery in the current modernization. The results of the study so far indicated that the young Catholics has tried their best to develop and utilize the duties of the Catholic Church ministery in the midst of the current of modernization in the way of utilizing technological and communication developments for digital-based proclamation of word of God and to organize various Catholics young’s activities in a more effective and efficient way.